Pengembangan E-Modul Persamaan Lingkaran Kelas XI MA dengan Menggunakan Aplikasi Heyzine - Muljo, Ariyani; Anggreni, Fenny; Maulida, Sari (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2024)
Abstract This research aims to determine the validity, practicality, and effectiveness of using the Heyzine application in teaching circular equations to 11th-grade students in senior high school. The research method employed the Four-D (Define, Design, Develop, Disseminate) development model developed by S. Thiagarajan, Dorothy Semmel, and Melvyn I. Semmel. Data collection involved documentation and questionnaires, while data analysis used a descriptive qualitative approach. The results showed that the e-module for mathematics instruction was deemed highly valid by experts and practitioners. The validity percentages of the e-module were as follows: 82.5% for subject matter experts with the criteria "very valid," 89% for media experts with the criteria "very valid," 85% for language experts with the criteria "very valid," and 82.75% for practitioners with the criteria "very valid." Thus, the overall validity averaged 84.81% with the criteria "very valid." The mathematics e-module on circular equations was also evaluated to meet usability aspects. Student responses to the e-module's usability across 13 assessment aspects averaged 87.53%, indicating that the e-module fulfilled usability requirements in practice. The use of the Heyzine application in teaching circular equations was proven effective, as there was an increase in student learning interest after using the module. The increase in student interest in learning mathematics reached 37.679%. Therefore, this e-module can be considered an effective alternative for improving the teaching of circular equations to 11th-grade students in senior high school. Keywords: E-Module, Heyzine